High‐throughput light sheet tomography platform for automated fast imaging of whole mouse brain. Issue 9 (8th June 2018) - Yang, Xiong; Zhang, Qi; Huang, Fei; Bai, Ke; Guo, Yiming; Zhang, Yongsheng; Li, Ning; Cui, Yuting; Sun, Pei; Zeng, Shaoqun; Lv, Xiaohua
Abstract : Acquiring information of the neural structures in the whole‐brain level is vital for systematically exploring mechanisms and principles of brain function and dysfunction. Most methods for whole brain imaging, while capable of capturing the complete morphology of neurons, usually involve complex sample preparation and several days of image acquisition. The whole process including optical clearing or resin embedding is time consuming for a quick survey of the distribution of specific neural circuits in the whole brain. Here, we develop a high‐throughput light‐sheet tomography platform (HLTP), which requires minimum sample preparation. This method does not require optical clearing for block face light sheet imaging. After fixation using paraformaldehyde, an aligned 3 dimensional image dataset of a whole mouse brain can be obtained within 5 hours at a voxel size of 1.30 × 1.30 × 0.92 μm. HLTP could be a very efficient tool for quick exploration and visualization of brain‐wide distribution of specific neurons or neural circuits. Abstract : An inclined light sheet microscopy‐based imaging platform is described. Image datasets with cellular resolution of a whole mouse brain can be obtained automatically in less than 5 hours with the proposed platform. Minimum sample preparation is needed. It is suitable for quick surveys of the distribution of specifically labeled neural circuits at a whole brain level.